Development of duplex polymerase chain reaction for detection of Vibrio alginolyticus infection in marine fish - Khairul Parman, Diyana Nadhirah (2017)
Vibrio alginolyticus species are among key pathogens that causes Vibriosis in a marine culture that can eventually lead to problems in food safety and bacterial disease management.In this study, an effective duplex PCR was developed for simultaneous and rapid detection species specific toVibrio alginolyticus by using gyrB and collagenase genes. The gyrB and collagenase genes were amplified using purified genomic DNA of V. alginolyticus and other Vibrio species with an estimated size of 337 bp and 737 bp respectively. The gyrB gene was specifically detected for all Vibrio sp and collagenase gene was specifically detected only for V. alginolyticus. The PCR products were cloned and sequenced. The Vibrio species and non-Vibrio species were conducted to specificity test, and it revealed that the primer sets were specific to V. alginolyticus and Vibrio species only. The sensitivity test was accomplished with various DNA concentrations of V. alginolyticus (100pg to 1pg), resulting in the lowest value of 1pg. The developed duplex PCR was also tested against artificial infection of groupers that were injected with 1010CFU/ml of V. alginolyticus, V. parahaemolyticus, and A.hydrophila. At 24 hours post-injection, the organs (liver, spleen, and kidney) were homogenized and a colony bacterium on TCBS agar was used in duplex PCR assay.All pairs of primers were shown to be specific and sensitive to V. alginolyticus and able to amplify collagenase and gyrB genes at 737 bp and 337 bp respectively. The result of artificially infected groupers showed that the duplex PCR was able to detect V. alginolyticus. The efficacy of this duplex PCR assay was confirmed from collected diseased groupers from the aquatic environment. It showed that duplex PCR assay was able to amplify gyrB gene for only 12 samples of Vibrio species, however no amplification was observed for collagenase gene. Therefore, these 12 samples were sent for sequenced and ran for BLASTn analysis. Based on the analysis, only two isolates were correctly identified as V. alginolyticus strains (BK5G3 and BK3G1). The extracted DNA of V. alginolyticus strains (BK5G3 and BK3G1) were subjected to duplex PCR assay and the result showed no amplification of collagenase gene. To confirm the presence of collagenase gene, the experiment was further carried out using Lates calcarifer as a fish model. However, no amplification was observed for collagenase gene. Therefore, the newly developed duplex PCR assay is able to be used in-vivo but unable to be apply in in-vitro study. Newly developed duplex PCR assay is, therefore, possible to use in food security analysis and disease detection of aquatic animals.